Towards a Catalog of Usability Smells - Almeida, D. (2015)
This paper presents a catalog of smells in the context of interactive applications. These so-called usability smells are indicators of poor design on an application’s user interface, with the potential to hinder not only its usability but also its maintenance and evolution. To eliminate such usability smells we discuss a set of program/usability refactorings. In order to validate the presented usability smells catalog, and the associated refactorings, we present a preliminary empirical study with software developers in the context of a real open source hospital management application. Moreover, a tool that computes graphical user interface behavior models, giving the applications’ source code, is used to automatically detect usability smells at the model level.